Emergency action for chemical and biological warfare agents - Ellison, D. Hank (CRC Press, 2016)
In the real-life world of emergency response, nothing is more crucial to crisis personnel than quick and decisive action. D. Hank Ellison's Emergency Action for Chemical and Biological Warfare Agents tells police, paramedics, and firefighters just what actions to take in the event of a crisis involving hazardous materials.